Animal Rights Activism - Jacobsson, Kerstin (Protest and Social Movements, 2017)
We're in an era of ever increasing attention to animal rights, and activism around the issue is growing more widespread and prominent. In this volume, Kerstin Jacobsson and Jonas Lindblom use the animal rights movement in Sweden to offer the first analysis of social movements through the lens of Emile Durkheim's sociology of morality. By positing social movements as essentially a moral phenomenon-and morality itself as a social fact-the book complements more structural, cultural, or strategic action-based approaches, even as it also demonstrates the continuing value of classical sociological approaches to understanding contemporary society.